Unlawful Acts According to Civil Law and Criminal Law - Aditya, Agung; Rakhmatika, Devi; Faradany Saputri, Nabila (Universitas Negeri Semarang, 2023)
Land grabbing is not a new phenomenon and has occurred in Indonesia. The term